Inovasi Pelayanan Kepegawaian Melalui Aplikasi Rumah ASN di Badan Kepegawaian Daerah Provinsi Jawa Timur - Anisa Dwi Asmaranti; Eva Hany Fanida; Meirinawati; Trenda Aktiva Oktariyanda (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Digital transformation in public service delivery encourages government to implement service innovations that are effective, efficient, transparent, and accountable. This transformations is realized through the adoption of innovations capable of responding to public needs in a timely and accurate manner to improve service quality. The Regional Civil Service Agency of East Java Province developed the Rumah ASN Application as a digital-based personnel service innovation to support the needs of civil servants of the East Java Provincial Government and the general public. This study aims to analyze and describe the implementation of the Rumah ASN Application as an innovation in personnel services at the Regional Civil Service Agency of East Java Province. This research employs a qualitative descriptive. The analytical framework is based on the public sector process innovation theory proposed by Khodadad-Saryazdi (2022), which consists of seven key success factors: strategic alignment, governance, leadership, culture, information technology and information system, process actors, and performance evaluation. Data were collected through interviews, observations, and documentation. The findings indicate that the implementation of the Rumah ASN Application has generally been conducted well, but it has not yet reached optimal. Challenges identified for optimizing this service including the needs for continuous user socialization during system updates, optimization of service features for civil servant capacity building, strengthening administrative capacity and cross-sectoral coordination, and the developing the application into a mobile application version.